Exercise-induced myocardial edema in master triathletes: Insights from cardiovascular magnetic resonance imaging - Ricci, Fabrizio; Aquaro, Giovanni Donato; De Innocentiis, Carlo; Rossi, Serena; Mantini, Cesare; Longo, Francesca; Khanji, Mohammed Y.; Gallina, Sabina; Pingitore, Alessandro (Frontiers in Cardiovascular Medicine, 2022)
Background Strenuous exercise has been associated with functional and structural cardiac changes due to local and systemic inflammatory responses, reflecting oxidative, metabolic, hormonal, and thermal stress, even in healthy individuals. We aimed to assess changes in myocardial structure and function using cardiovascular magnetic resonance (CMR) imaging in master triathletes early after a full-distance Ironman Triathlon race. Materials and methods Ten master triathletes (age 45 ± 8 years) underwent CMR within 3 h after a full-distance Ironman Triathlon race (3.8 km swimming, 180 km cycling, and 42.2 km running) completed with a mean time of 12 ± 1 h. All the triathletes had a 30-day follow-up CMR. Cine balanced steady-state free precession, T2-short tau inversion recovery (STIR), tagging, and late gadolinium enhancement (LGE) imaging sequences were performed on a 1.5-T MR scanner. Myocardial edema was defined as a region with increased T2 signal intensity (SI) of at least two SDs above the mean of the normal myocardium. The extent of myocardial edema was expressed as the percentage of left ventricular (LV) mass. Analysis of LV strain and torsion by tissue tagging included the assessment of radial, longitudinal, and circumferential peak systolic strain, rotation, and twist. Results Compared with postrace, biventricular volumes, ejection fraction, and LV mass index remained unchanged at 30-day follow-up. Global T2 SI was significantly higher in the postrace CMR (postrace 10.5 ± 6% vs. follow-up 3.9 ± 3.8%, P = 0.004) and presented with a relative apical sparing distribution (P < 0.001) matched by reduction of radial peak systolic strain of basal segments (P = 0.003). Apical rotation and twist were significantly higher immediately after the competition compared with follow-up (P < 0.05). Conclusion Strenuous exercise in master triathletes is associated with a reversible regional increase in myocardial edema and reduction of radial peak systolic strain, both presenting with a relative apical sparing pattern.